Hellenistic and Biblical Greek : a graduated reader - McLean, Bradley H. (Bradley Hudson), 1957- (Cambridge Cambridge University Press, 2014)
"This Hellenistic Greek reader is designed for students who have completed one or more years of Greek and wish to improve their reading ability and gain a better appreciation for the diversity of the language. The seventy passages in this reader reflect different styles, genres, provenances, and purposes, and are arranged into eight parts according to their level of difficulty. Grammatical support and vocabulary lists accompany each passage, and a cumulative glossary offers further assistance with translation. Students are led to a deeper understanding of Hellenistic Greek, and a greater facility with the language. Includes canonical and non-canonical Christian texts, Septuagint (prose and poetry), Jewish Pseudepigrapha, inscriptions, and Jewish and Hellenistic literary Greek. Includes a Web component with more than thirty additional readings for classroom and independent use. Offers a glimpse into the everyday life of Hellenistic Greeks, with themes such as sexuality, slavery, magic, apocalypticism, and Hellenistic philosophy"--
Machine generated contents note: Introduction; 1. Basic level: early Christian texts; 2. Basic level: the isometric translational Greek of the Septuagint (prose and poetry); 3. Intermediate level: Jewish recensional Greek; 4. Intermediate level: Hellenistic Greek; 5. High intermediate level: Hellenistic Greek; 6. Advanced level Hellenistic Greek: Jewish literary Greek; 7. Advanced level: Inscriptions; 8. Advanced level Hellenistic Greek: Atticizing and literary Greek; 9. Summary of verbal paradigms; Glossary.
Includes bibliographical references, glossary, and index.
Keywords: Bible. -- Language, style -- Problems, exercises, etc; Greek language, Hellenistic (300 B.C.-600 A.D.) -- Readers; Greek language, Hellenistic (300 B.C.-600 A.D.) -- Grammar; Greek language, Biblical -- Readers; Greek language, Biblical -- Grammar; FOREIGN LANGUAGE STUDY / Ancient Languages (see also Latin).